Mitsunobu Reactions of 5‐Fluorouridine with the Terpenols Phytol and Nerol: DNA Building Blocks for a Biomimetic Lipophilization of Nucleic Acids. Issue 12 (December 2013) - Malecki, Edith; Knies, Christine; Werz, Emma; Rosemeyer, Helmut
Abstract The cancerostatic 5‐fluorouridine (5‐FUrd; 1) was sequentially sugar‐protected by introduction of a 2′, 3′‐O‐heptylidene ketal group (→2), followed by 5′‐O‐monomethoxytritylation (→3). This fully protected derivative was submitted to Mitsunobu reactions with either phytol ((Z and E)‐isomer) or nerol ((Z)‐isomer) to yield the nucleoterpenes 4a and 4b. Both were 5′‐O‐deprotected with 2% Cl2CHCOOH in CH2Cl2 to yield compounds 5a and 5b, respectively. These were converted to the 5′‐O‐cyanoethyl phosphoramidites 6a and 6b, respectively. Moreover, the 2′, 3′‐O‐(1‐nonyldecylidene) derivative, 7a, of 5‐fluorouridine was resynthesized and labelled at C(5′) with an Eterneon‐480 fluorophor® (→7b). The resulting nucleolipid was studied with respect to its incorporation in an artificial bilayer, as well as to its aggregate formation. Additionally, two oligonucleotides carrying terminal phytol‐alkylated 5‐fluorouridine tags were prepared, one of which was studied concerning its incorporation in an artificial lipid bilayer.